2001
DOI: 10.1053/jhep.2001.22347
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 10 polymorphisms as predictors of sustained response in antiviral therapy for chronic hepatitis C infection

Abstract: Host genetic factors have been reported to influence the natural history of hepatitis C virus (HCV) infection. We examined whether variation in interleukin 10 (IL-10) and tumor necrosis factor ␣ (TNF-␣) genes would predict the likelihood of sustained response to antiviral therapy. Single nucleotide polymorphisms (SNPs) and microsatellites at two loci encoding the cytokines IL-10 and TNF-␣ were determined by polymerase chain reaction (PCR)-based techniques. Their relationship to the outcome of antiviral therapy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
137
5
3

Year Published

2003
2003
2010
2010

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 192 publications
(150 citation statements)
references
References 50 publications
5
137
5
3
Order By: Relevance
“…There were two haplotypes in the IL19/IL20 region in African Americans significantly associated with HCV clearance, the depleted CTGAAC (OR ¼ 0.56-0.59, P ¼ 0.05-0.04) and the enriched TCAGGC (OR ¼ 1.93-2.7, P ¼ 0.01-0.002). In addition, as a test of association of extended haplotypes in the promoter region with HCV, [38][39][40][41] we analyzed the association of well-studied proximal 46 and distal haplotypes 45 and HCV clearance (Table 4). These results indicated that distal haplotypes AAA (OR ¼ 0.38, P ¼ 0.002-0.003), and TGC (OR ¼ 1.52, P ¼ 0.04-0.03), but not proximal haplotypes in IL10 are associated with clearance of HCV in the AfricanAmerican population.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There were two haplotypes in the IL19/IL20 region in African Americans significantly associated with HCV clearance, the depleted CTGAAC (OR ¼ 0.56-0.59, P ¼ 0.05-0.04) and the enriched TCAGGC (OR ¼ 1.93-2.7, P ¼ 0.01-0.002). In addition, as a test of association of extended haplotypes in the promoter region with HCV, [38][39][40][41] we analyzed the association of well-studied proximal 46 and distal haplotypes 45 and HCV clearance (Table 4). These results indicated that distal haplotypes AAA (OR ¼ 0.38, P ¼ 0.002-0.003), and TGC (OR ¼ 1.52, P ¼ 0.04-0.03), but not proximal haplotypes in IL10 are associated with clearance of HCV in the AfricanAmerican population.…”
Section: Resultsmentioning
confidence: 99%
“…36 The commercial IFN-a preparations that are largely used for HCV therapy consist of IFN-a2a or IFN-a2b subtypes. 37 Some of these studies indicate that there is a positive IL10 association with susceptibility to chronic hepatitis C infection and resistance to combined antiviral therapy [38][39][40][41] and rapid fibrosis 39 while in others the association between IL10 promoter region SNPs and viral clearance or persistent infection or severity of disease was not found. [42][43][44] These results further indicated the importance of evaluating HCV clearance in a large set of patients for IL10, its neighboring paralogs, and other genes in the region.…”
Section: Introductionmentioning
confidence: 99%
“…Pharmacogenetic studies should be useful in elucidating such individual and ethnic disparities in response to HCV therapy. 6,7 The main expectation is that recognition of reliable genetic markers will substantially improve intervention strategies through individualization of therapeutic regimens, thereby reducing costs and avoiding debilitating complications. These studies also hold the promise of identifying additional molecular mechanisms that can be targeted for new, more effective interventions.…”
Section: Heterogeneity In Response To Hcv Therapymentioning
confidence: 99%
“…In those analyses of more than a single SNP or mutation in more than 100 patients, preliminary genetic markers include HLA and related variants on chromosome 6, 12,13 homozygosity for an extended haplotype (HHE) along the CCR2 to CCR5 loci on chromosome 3, 14 as well as cytokine gene and related polymorphisms mapped to various locations. [6][7][8] For example, HLA-DRB1*07 was associated with the NR phenotype in treated French (n ¼ 170), 12 while Japanese patients (n ¼ 175) with the LMP7 variant that changes amino acid 49Gln to 49Lys were more likely to be sustained responders (SRs). 13 In CTLA4, the 49G variant on the (À381)C-49G haplotype has been associated with SR in one study of European Americans (n ¼ 158).…”
Section: Additional Leadsmentioning
confidence: 99%
See 1 more Smart Citation